2022
DOI: 10.1016/j.jceh.2021.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Management of Refractory Variceal Bleed in Cirrhosis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The standard management for variceal bleeding includes red blood cell transfusion (without transfusion overload), prophylactic antibiotics, and oral nutrition. 38 In randomized controlled trials (RCTs), lactulose and rifaximin were shown to be effective for the treatment of HE. 39,40 Patients with suspected variceal bleeding must receive vasoactive drugs, such as terlipressin.…”
Section: Prevention and Treatment Of Bleeding As Precipitantmentioning
confidence: 99%
“…The standard management for variceal bleeding includes red blood cell transfusion (without transfusion overload), prophylactic antibiotics, and oral nutrition. 38 In randomized controlled trials (RCTs), lactulose and rifaximin were shown to be effective for the treatment of HE. 39,40 Patients with suspected variceal bleeding must receive vasoactive drugs, such as terlipressin.…”
Section: Prevention and Treatment Of Bleeding As Precipitantmentioning
confidence: 99%
“…According to Wang et al, BRTO was not more challenging to complete than TIPS [ 48 ]. In addition, Othita et al [ 49 ] reported that for all patients, splenectomy with gastric devascularization significantly increased overall survival (OS) compared to BRTO [ 3 ]. The two groups' rates of rebleeding occurrence were the same.…”
Section: Reviewmentioning
confidence: 99%
“…Gastrointestinal bleeding is often encountered in patients with cirrhosis, with an incidence of 85% in Child Class C versus 45% in Child Class A [ 2 ]. Patients in Child Class C also have up to 30% mortality risk compared to other classes [ 3 ]. Nearly half of the patients diagnosed with liver cirrhosis have already developed gastroesophageal varices, which can lead to variceal bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…67,69,79 In about 10%-20% patients, AVB cannot be controlled or reoccurs despite adequate endoscopic interventions or timely vasoconstrictor therapy. 80,81 For patients in whom an early TIPS is not performed, intravenous vasoactive drugs should be continued for 2-5 days and NSBBs initiated once vasoactive drugs are discontinued. Rescue TIPS is indicated in these patients if hemorrhage cannot be controlled or if bleeding recurs despite vasoactive drugs.…”
Section: Gastroesophageal Varicesmentioning
confidence: 99%